Role of mitochondria-associated membranes (MAMs) in inflammatory signaling: implications for acute lung injury pathogenesis - Qian, Huifeng; Qiu, Guanguan; Xu, Jianguo; Zheng, Guoping (Frontiers in Cell and Developmental Biology, 2025)
Mitochondria-associated membranes (MAMs), the specialized contact regions linking the endoplasmic reticulum (ER) and mitochondria, have emerged as dynamic communication hubs critical for preserving cellular homeostasis. These structures are crucial for controlling a range of essential cellular processes, such as calcium (Ca2+) signaling, lipid metabolism, autophagy, apoptosis, and inflammatory response. Increasing evidence connects MAM dysfunction to various inflammatory conditions, such as metabolic disorders, neurodegenerative diseases, and antiviral response. In the context of acute lung injury, altered ER–mitochondria interactions can result in mitochondria Ca2+ overload, heightened oxidative stress, and augmented inflammatory response. Together, these pathological processes enhance endothelial permeability and exacerbate pulmonary inflammation. This review highlights the structural and functional attributes of MAMs, the mechanisms underlying MAM-mediated inflammation, and the roles of MAMs in metabolic, neurological, and antiviral inflammation. It also delves into the role of MAMs in acute lung injury, unveiling fresh insights that may pave the way for innovative therapies targeting ER–mitochondria crosstalk.